KINERJA PELAYANAN PUBLIK PADA KANTOR CAMAT RUMBAI KOTA PEKANBARU - Suryani, Fatwa; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The deliveryof public servicesinIndonesia is stillfarfrom theexpectations ofcitizens. Their aspirationstoobtaingoodqualitypublic servicesseemsstillunclear when it willhappen. To realizegood public serviceas expectedcitizensmustbe supportedbygood performance. Torealize theincreasing demands ofgood performanceis notan easy matterfor the region, needsimprovementeffortsstill need tobe implementedtoachievea quality service. Public servicesplay a critical roleinanorganization, becausethe good and badof an organizationdepends onthe services provided tothe communityas well as possible, so that peoplereceivetheservicescanbe satisfiedwith the services provided.The purpose of this study was to analyze the Public Service Performance At Camat Office Rumbai Pekanbaru. To analyze the performance of public services in the District of Tassel views of responsiveness, responsibiltas, and accountability.This research was conductedat theHead OfficeRumbaiPekanbaru Citywho becameinformantsin this studyis asub-district, sub-districtsecretary, Head ofGovernment,Head ofthe Public Service, Head ofpeaceandpublic order, Head ofFMD, Head ofSocial Welfare. Incollectingthe datauseda qualitative approachwiththe method of observationandin-depthinterviews, after thedata iscollected thenanalyzeddescriptively.Thusthe conclusionsobtainedfromthis studyfoundthatthe performance ofsub-districtsin providing public servicesto the communityhas notfullydone wellandis influencedbyseveralfactors:leadership, organizationalculture, organizational capabilitiesandthe externalenvironment.Keywords: Performance, Public Service, District Office Rumbai of Pekanbaru